Modern power station practice. (Pergamon, 1971)
Modern Power Station Practice, Volume 5: Chemistry and Metallurgy focuses on power station chemistry and metallurgy. The book first offers information on power station chemistry, including the use, preparation, sampling, storage, and transport of coal to power stations. Other considerations include the commercial use of ash, analysis and testing of coal and coke, gas-side cleaning of boilers, oil firing, burner fuels, testing of fuel oils and gases, and air pollution. The text also reviews water treatment relative to the operation of boilers. The corrosion of metals; sampling and analysis of f.